Assessment of antibiotics use after introducing a hospital formulary by ATC/DDD methodology (Medical Journal of Indonesia, 2004)
The objective of this study is to compare the use of antibiotics at the Metropolitan Medical Center Hospital in Jakarta, Indonesia (MMCH), before and after the implementation of a hospital formulary. All antibiotic data under J01 Anatomical Therapeutic Chemical (ATC) classification were collected from pharmacy inpatient and outpatient records. Quantitative antibiotic use was expressed in Defined Daily Doses/100 bed-days (DDDs/hbd) for inpatients and DDDs/1000 patients/day (DDDs/tpd) for outpatients. The general quality of drug use was assessed in number of drugs that account for 90% of the use (DU90%) and the adherence to hospital formulary by substance and brand name within the DU90% segment. Quantitative and qualitative antibiotic use were compared before and after implementation of the formulary (1999 to 2000). The Wilcoxon rank sign test was used to compare overall antibiotic use. Inpatient antibiotic usage decreased significantly by 23.1%, 124.96 DDDs/hbd in 1999 to 96.13 DDDs/hbd during 2000 (p= 0.03) and outpatient antibiotic usage decreased insignificantly by 4.9%, 3.49 DDDs/tpd during 1999 to 3.32 DDDs/tpd during 2000 (p=0.58).The most commonly antibiotic use was ciprofloxacin in inpatient setting during the study and in out-patient setting was amoxicillin in 1999 and ciprofloxacin in 2000. The adherence to the formulary by substance and by brand name in inpatient department was 100% and 90.5% and in outpatient department was 100% and 94.3% during the study. DU 90% by substance name and by brand name was considerably not improved in both settings. The conclusion is that the effectiveness of one year formulary implementation at MMCH was only revealed in inpatient setting. (Med J Indones 2004; 13: 173-9) Keywords: antibiotic use, hospital formulary